The clinical intervention choice for pediatric tic disorder patients from a tertiary children's hospital in China: a large-scale retrospective study based on electronic medical records. (July 2021) - Wang, Fang; Ma, Zihan; Li, Ying; Wen, Fang; Yu, Liping; Yan, Junjuan; Liu, Jingran; Zhang, Jishui; Cui, Yonghua
Abstract : Supplemental Digital Content is available in the text. Abstract : Pharmacological intervention played an important role in the management of tic disorder. Large-scale prescription data for pediatric tic disorder patients in the real-world setting were scarce. The demographic and prescription data of tic disorder were extracted from the electronic medical records database of Beijing Children's Hospital from 2018 to 2020. The intervention choice for outpatient pediatric tic disorder patients was analyzed. A total of 20 417 patients were included, 28.1% (n = 5028) of them did not receive any pharmacological treatment. Over 70% were prescribed with anti-tic medication. For children less than 6 years of age, clonidine adhesive patches (CAPs) and traditional Chinese medicine (TCM) were the common choice. With the age growing, the use of antipsychotics was on the rise; 22% (n = 3389) were prescribed for at least two anti-tic medication, and the most common medication combination group was tiapride and TCM (33.7%), followed by CAP and TCM (22.1%). The clinical intervention choice for tic disorder is highly individualized. The pharmacological choice was influenced by severity, duration of symptom, age, the acceptance of parents and other factors.